Insights into the mechanical properties and fracture mechanism of Cadmium Telluride nanowire. (30th August 2019) - Munshi, Md Adnan Mahathir; Majumder, Sourajit; Motalab, Mohammad; Saha, Sourav
Abstract: Semiconducting nanowires (NWs), key building blocks in nanotechnology with many potential applications, are stirring the attention of the scientific world because of their many unique properties. Cadmium telluride ( CdTe ) single crystal nanowires, with Zinc Blende (ZB) crystal configuration, have become the focus of interest nowadays due to its promising application in Opto-electro-mechanical nanodevices. However, due to the lack of complete insight into their mechanical deformation, it is necessary to thoroughly study the CdTe nanowires. In this study, molecular dynamics simulations have been used to investigate the mechanical behavior of CdTe nanowires (NWs) by varying size, temperature, crystal orientation, and strain rate under tension and compression. Results show that the fracture strength of the [111]-oriented CdTe NWs is always higher than that of the [110]-oriented CdTe NWs under tension whereas, in compression, the fracture strength of the [111]-oriented CdTe NWs is significantly lower than that of the [110]-oriented CdTe NWs. Moreover, upon applying the tensile load along NWs growth direction, the [111]-oriented CdTe NWs fail by creating void in [10-1] direction due to bond breaking in [1-21] direction regardless of temperature and NW size. Under compression, the [111]-oriented nanowires show buckling and plasticity. It has also been observed that size has a negligible effect on the tensile behavior but in compression, the behavior is size-dependent. Both tensile and compressive strengths show an inverse relation with temperature. Finally, the impact of strain rate on [111]-oriented CdTe NWs are also studied where higher fracture strengths and strains at higher strain rates have been found under both tension and compression. With increasing the strain rate, the number of voids is also increased in the NWs. This study will help to design CdTe NWs based devices efficiently by presenting an in-depth understanding of the failure behavior of the [111]-oriented CdTe NWs.